NETIZEN'S LANGUAGE POLICY IN COMMENTING NADIEM MAKARIM INSTAGRAM ACCOUNT ABOUT ONLINE LEARNING - Yustitiayu Novelly; Syahrul R.; Amril Amir (Universitas Negeri Makassar, 2021)
The purpose of this study is to see how polite netizens are in commenting on Nadiem Makarim's Instagram account, Minister of Education and Culture. This type of research is a qualitative research with descriptive method. The data is sourced from the Instagram account (@nadiemmakariem), speech or writing in the comments of Nadiem Makarim's first post on August 17, 2020, the focus of the data is comments about online learning. The results showed that comments about online learning on Nadiem Makarim's posts were dominated by netizens who used polite speech or obeyed the principles of politeness. Comments that are found a lot are comments from school children and students for schools to be reactivated or they want schools to be opened and face to face. This is certainly a spirit that appears from the students and a positive thing. Complying with the netizen's politeness principle in commenting on Nadiem Makarim's Instagram account, there are 85 utterances or comments. Meanwhile, there are 54 violations of the netizen's politeness principles.